PENERAPAN PRINSIP SUSTAINABLE DEVELOPMENT PADA PERANCANGAN PONDOK PESANTREN ENTERPRENEUR - Annur, Achmad Siddiq; Mappaturi, Andi Baso (Journal of Islamic Architecture, 2012)
Unhealthy competition among economic actors, and exploitation of natural resources without preservation,caused a complicated problem in the community. Poor-quality education, especially in moral and religiouseducation, to be one of the causes of these problems. Therefore, the existence of boarding school as aneducational institution based on Islam is expected to be a solution to decline moral values and religion in thisnation. Through a combination of formal and religious education at a boarding school will provide a strongmental training for the formation of individual intelligent and noble. In addition, a boarding school with speechentrepreneurship curriculum in the education system, can provide an added value to the institution.Prospective employers are responsible for each other and the environment, and economic actors are honestand committed. Entrepreneur Boarding can be part of an effort to maintain the sustainability of resources,both natural and human resources. Sustainable development, as the purpose of the object, is a theme thatdescribes every aspect of the design object. Sustainable development has three principles of sustainability; thenatural environment sustainability, social sustainability and economic sustainability. Starting from the planningof design, the building process, until the use of the building, always accompanied by the consideration of thethree aspects of sustainability. Through the application of sustainable development as the design theme of theboarding school entrepreneurs will produce buildings that are environmentally and socially friendly, in additionto continue to provide investment for owners, users, and the surrounding community.